(untitled) (Global Media Journal - German Edition, 2012)
In order to investigate the relationship between censorship and popular uprisings, I survey trends in repression of information across Iran and the Arab states of the Middle East & North Africa over several decades to see if the recent wave of popular mobilization appears to respond to changes in the degree of repression in particular countries. I argue that while the available data is inconclusive, there is little support for the idea that partial liberalization provokes revolutionary outbreaks and conversely some support for high or increasing repression of expression as a contributor to regime-challenging popular mobilization.